Dampak Program Otago Home Exercise terhadap Penurunan Risiko Jatuh pada Lansia - Purnama, Heni; Ropikoh, Popi Bunga; Vita Lucya (LPPM Universitas Pekalongan, 2025)
Background: The elderly, defined as individuals aged 60 years and older, experience various physiological changes associated with aging. One significant change is the decline in bodily functions, which affects the body's ability to adapt to the environment and often leads to impaired balance. This condition increases the risk of falls, making fall prevention efforts essential. One such effort is the Otago Home Exercise Programme (OHEP), a structured balance and strength training intervention. Purpose: This study aimed to determine the effect of OHEP on fall risk in the elderly. Methods: A quasi-experimental design with two groups and pretest–post-test. The samples involving 60 participants selected through purposive sampling. The intervention was conducted three times a week for three weeks, and fall risk was measured using the Timed Up and Go Test (TUGT). Data were analysed using the Wilcoxon and Mann-Whitney tests. Results: Results showed a significant reduction in fall risk in the intervention group, with high risk decreasing from 10% to 0%, moderate risk from 90% to 80%, and an increase in low risk from 0% to 20% (p = 0.000). Conclusion: It can be concluded that OHEP is effective in reducing fall risk among the elderly and is recommended for wider implementation in elderly care settings.